2015
DOI: 10.1007/s10439-015-1377-5
|View full text |Cite
|
Sign up to set email alerts
|

Simulated Thrombin Generation in the Presence of Surface-Bound Heparin and Circulating Tissue Factor

Abstract: An expanded computational model of surface induced thrombin generation was developed that includes hemodynamic effects, 22 biochemical reactions and 44 distinct chemical species. Surface binding of factors V, VIII, IX, and X was included in order to more accurately simulate the formation of the surface complexes tenase and prothrombinase. In order to model these reactions, the non-activated, activated and inactivated forms were all considered. This model was used to investigate the impact of surface bound hepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 51 publications
1
14
0
Order By: Relevance
“…We have previously demonstrated that shear rate influences the TF surface density required to generate a threshold concentration of thrombin that is sufficient to propagate the cascade. 18, 22 This observation supports the notion that mass transport has an important impact on the sensitivity of a given hemodynamic environment to generate thrombin induced by surface-bound TF. Each of the TF positions considered in these studies experiences different mass transport conditions, as a consequence of the large vortex near the valve opening (Figure 1D).…”
Section: Resultssupporting
confidence: 75%
See 3 more Smart Citations
“…We have previously demonstrated that shear rate influences the TF surface density required to generate a threshold concentration of thrombin that is sufficient to propagate the cascade. 18, 22 This observation supports the notion that mass transport has an important impact on the sensitivity of a given hemodynamic environment to generate thrombin induced by surface-bound TF. Each of the TF positions considered in these studies experiences different mass transport conditions, as a consequence of the large vortex near the valve opening (Figure 1D).…”
Section: Resultssupporting
confidence: 75%
“…22 In short, the presence of surface-bound TF initiates the cascade by reversibly binding to activated factor VIIa, forming extrinsic tenase. Extrinsic tenase activates factor X and IX, where activated factor Xa activates factors VII and V. Surface species prothrombinase is formed by the binding of activated factors Xa and Va. Prothrombinase, in turn, activates factors VII, as well as factor II (prothrombin) producing thrombin.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Heparin upregulates the activity of antithrombin which reduces blood coagulability. In a recent work [30], Dydek and Chaikof equipped a previously developed model for in situ clot growth with the action of heparin. The resulting model is detailed and focuses on the spatio-temporal dynamics of clot growth during heparin treatment.…”
Section: Pk-pd and Systems Pharmacology In Blood Clotting Pathologiesmentioning
confidence: 99%